Antihyperlipidemic activity and mechanism test of cashew nut shell extract in male wistar rat induced by high-cholesterol foods - Era Rahmi; Poppy Dharsana (Universitas Muhammadiyah Malang, 2021)
Nutshell is a waste of cashew nuts product which is known to contain phytosterols was tested as an antihyperlipidemic agent with two methods: induction of hyperlipidemia and inhibition of cholesterol absorption method. In induction of hyperlipidemia, animals were induced using high cholesterol foods and induction agents (cholesterol, cholic acid, and propylthiouracil). After that were treated using simvastatin and cashew nut shell extract. Total cholesterol value was measured periodically after therapy, then aorta was isolated to examine the histology of aorta. In inhibition cholesterol absorption method, rats were given PTU and then were given ezetimibe and extracted orally. After that, all the animals were induced with exogenous cholesterol. Cholesterol level in the serum and feces was measured as well as to see the effects of inhibition of cholesterol absorption. For hyperlipidemia induction method, extract had different significance compared to the control group after 8 weeks of therapy. Atherogenic index of plasma (IAP) values of low-dose extract and high dose extract was significantly different compared to the control group. Histology of rats aorta for extract was significantly different in thickness compared to the control group. In the inhibition of cholesterol absorption method, extract 250mg/kg bw (group EKBKM 250) and 500 mg/kg bw (group EKBKM 500) inhibit the increase of total blood cholesterol within one hour after induction and significantly different compared to the control group. N-hexane extract cashew nut shells 500mg/kg have antihyperlipidemic effects, one of them is inhibition of cholesterol absorption.